Research of causes of low IPO number in the Czech Republic - Tomáš Meluzín (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
Funding development of the company through the “Initial Public Offering” has a high representation globally, the Czech Republic unlike, and belongs to traditional methods of raising funds necessary for development of business in the developed capital markets. In the United States of America, Japan and in the Western Europe countries the method of company funding through IPO has been applying for several decades already. The first public stock offerings began to be applied in these markets in higher volumes from the beginning of the 60th of the last century. From that period importance of IPO goes up globally and the initial public stock offerings begin to be applied more and more even in the Central and Eastern European countries. Under the conditions of the Czech capital market this way funding of development of the company, connected with its entering into the capital market, is not very usual. The Strategy of Sustainable Development of the Czech Republic considers this situation the weakness of the Czech economy, and its resolving has to be paid a due care. The present paper introduces the results of an analysis identifying the causes of the low numbers of IPOs in the Czech Republic. These causes were analyzed in a comprehensive way covering the period of time from the beginnings of the modern-day capital market in the Czech Republic until the present times. In order to reach the objective, the secondary research of the literature sources, focused on the issue in question and the primary research in the Czech companies was carried out.